Optimisation of physical parameters and microbial community analysis of bio-hydrogen production from food waste - Mohd Yasin, Nazlina Haiza (2021)
The demand for clean energy from renewable resources stimulates biohydrogen production from biomass as an alternative fuel to replace fossil fuel. Biohydrogen from food waste fermentation initiates clean technologies for energy generation thus provide the solution for waste treatment. However, the production of biohydrogen is inhibited by hydrogen consuming bacteria and soluble metabolites. This inhibition effects can be overcome by optimizing the physical parameters during biohydrogen production. The objectives of this study were to establish the optimum operating parameters for biohydrogen production from food waste in batch fermentation and to identify the main hydrogen-producing bacteria at different controlled pH values. The batch fermentation was conducted using 150 mL serum bottles incubated in facultative anaerobic condition. Cooked and uncooked food waste taken from cafeterias with composition ratios of 2: 1:1 carbohydrate, protein and fiber were used as a substrate in this study. The concentration of food waste was standardized at 25 gil carbohydrate before all the experiments was conducted. Palm oil mill effluent (PO ME) sludge was used as a seed culture. Heat treatment was carried out to POME sludge at 80°C for 30 minutes to eliminate hydrogen consuming bacteria. Biohydrogen production was performed at different temperatures (35°C, 40°C, 50°C, 55°C and 60°C), initial pH values (5, 6, 7 and 8) and various ratios of sludge to substrate (10:90, 20:80, 30:70 and 40:60 % (v/v)). Biogas was collected every 2 h and the composition of hydrogen and carbon dioxide in biogas was analyzed by gas chromatography with no methane gas detected in all experiments. The highest biohydrogen yield obtained was 83 mmol I-h/L-medium/d for the experiment conducted at a temperature of 55°C, initial pH 7 and sludge to substrate ratio at 30:70 % (v/v). The experiment was then studied using different controlled pH values of 5.0, 5.5 and 6.0 at temperature of 55°C in 500 mL bioreactor. The results showed that pH 5.5 gave the highest biohydrogen production yield (79 mmol H2/L-medium/d). Microbial cells number was determined by using t1uorescent in situ hybridization (FISH) technique. The quantification analysis showed that the number of Clostridium sp. from cluster I and XI from samples after acclimatization was 2.9 x 108 cells/mL while the number of Clostridium sp. from fermentation medium at pH 5.0, 5.5 and 6.0 were 3.6 x 108, 7.8 x 108 and 5.4 x 108 cells/mL, respectively. Clostridium sp. from cluster I and XI were found to be dominant at pH 5.5 (92% out of the total bacteria) which corresponded to the highest biohydrogen yield compared to the other pH values. Clostridium sp. cluster I produce butyrate as the main metabolites while cluster XI criteria is heterogenous includes non-spore forming and thermotolerance alkaliphiles species. Methanogens were not detected in the culture broth due to the heat treatment. Microbial profile at different pH was also investigated using denaturing gradient gel electrophoresis (DGGE). It was revealed that the DGGE bands belonged to uncultured Bacteroidetes, uncultured bacterium, Caloramator australicus sp. and Clostridium sp. Thus, controlled operating conditions were important to enhance hydrogen-producing bacterial growth for optimum biohydrogen production.